Helicobacter pylori infection and low dietary iron alter behavior, induce iron deficiency anemia, and modulate hippocampal gene expression in female C57BL/6 mice. - Monika Burns; Aldo Amaya; Caroline Bodi; Zhongming Ge; Vasudevan Bakthavatchalu; Kathleen Ennis; Timothy C Wang; Michael Georgieff; James G Fox (PLoS ONE, 2017)
Helicobacter pylori (H.pylori), a bacterial pathogen, is a causative agent of gastritis and peptic ulcer disease and is a strong risk factor for development of gastric cancer. Environmental conditions, such as poor dietary iron resulting in iron deficiency anemia (IDA), enhance H.pylori virulence and increases risk for gastric cancer. IDA affects billions of people worldwide, and there is considerable overlap between regions of high IDA and high H.pylori prevalence. The primary aims of our study were to evaluate the effect of H.pylori infection on behavior, iron metabolism, red blood cell indices, and behavioral outcomes following comorbid H. pylori infection and dietary iron deficiency in a mouse model. C57BL/6 female mice (n = 40) were used; half were placed on a moderately iron deficient (ID) diet immediately post-weaning, and the other half were maintained on an iron replete (IR) diet. Half were dosed with H.pylori SS1 at 5 weeks of age, and the remaining mice were sham-dosed. There were 4 study groups: a control group (-Hp, IR diet) as well as 3 experimental groups (-Hp, ID diet; +Hp, IR diet; +Hp,ID diet). All mice were tested in an open field apparatus at 8 weeks postinfection. Independent of dietary iron status, H.pylori -infected mice performed fewer exploratory behaviors in the open field chamber than uninfected mice (p<0.001). Hippocampal gene expression of myelination markers and dopamine receptor 1 was significantly downregulated in mice on an ID diet (both p<0.05), independent of infection status. At 12 months postinfection, hematocrit (Hct) and hemoglobin (Hgb) concentration were significantly lower in +Hp, ID diet mice compared to all other study groups. H.pylori infection caused IDA in mice maintained on a marginal iron diet. The mouse model developed in this study is a useful model to study the neurologic, behavioral, and hematologic impact of the common human co-morbidity of H. pylori infection and IDA.